Secondary metabolites from Isodon ternifolius (D. Don) Kudo and their anticancer activity as DNA topoisomerase IB and Tyrosyl-DNA phosphodiesterase 1 inhibitors. Issue 11 (1st June 2020) - Zhang, Hong-Li; Zhang, Yu; Yan, Xue-Long; Xiao, Long-Gao; Hu, De-Xuan; Yu, Qian; An, Lin-Kun
Graphical abstract: Highlights: New compounds, isodopene A and isodopene B were isolated from the roots of I. ternifolius. Isodopene A and isodopene B showed strong (+++) and moderate (++) TOP1 inhibition. Two chalcones 11 and 12 were firstly found as dual TDP1 and TOP1 inhibitors. Three compounds 8, 16, and 22 acted as TOP1 catalytic inhibitors. Abstract: Based on DNA topoisomerase IB (TOP1) and tyrosyl-DNA phosphodiesterase 1 (TDP1) inhibition of the ethanol extract of the roots of Isodon ternifolius (D. Don) Kudo (Labiatae), its secondary metabolites has been studied. Two new compounds, an ent -abietane diterpenoid isodopene A (1 ) and a 2, 3- seco -triterpene isodopene B (13 ), along with 25 known compounds were isolated. Their structures were elucidated by spectroscopic analysis and theoretical calculations. The enzyme-based assays indicated that 1 and 13 showed strong (+++) and moderate (++) TOP1 inhibition, respectively. Two chalcone derivatives 11 and 12 were firstly found as dual TDP1 and TOP1 natural inhibitors, and showed synergistic effect with the clinical TOP1 inhibitors topotecan in MCF-7 cells. Compounds 8, 16, and 22 acted as TOP1 catalytic inhibitors with equipotent TOP1 inhibition to camptothecin (++++). Compounds 7 and 8 exhibited significant cytotoxicity against MCF-7, A549, and HCT116 cells with GI50 values in the range of 2.2–4.8 μM. This work would provide valuable information that secondary metabolites from I. ternifolius could be developed as anticancer agents.